Staging and Management of Cervical Cancer at the Colposcopy Clinic of Bangabandhu Sheikh Sheikh Mujib Medical University (BSMMU), Bangladesh - Nessa, Ashrafun; Islam, Thrina; Noor-E-Ferdousi, Noor-E-Ferdousi; Sultana, Anjuman; Khan, Kamrul Hasan; Rashid, Harun ur (South Asian Journal of Cancer, 2024)
Cervical cancer (CC) ranks as the second most common cancer among women in Bangladesh. Unfortunately, due to late-stage diagnosis and inadequate treatment facilities, the mortality rate remains high. The stage at which CC is diagnosed plays a crucial role in predicting a woman's survival. This study aimed to determine the staging patterns of CC at presentation in the colposcopy clinic of Bangabandhu Sheikh Mujib Medical University (BSMMU) and the subsequent management provided to these women. This retrospective study was conducted at the BSMMU colposcopy clinic from January 2019 to June 2020. It included CC cases with known staging, spanning from January 2016 to June 2019. Data were collected from the colposcopy registry book, telephone interviews, and face-to-face discussions during follow-up appointments. The mean age of women diagnosed with CC was 48.59 years (±2 standard deviations). Among the 523 women studied, 107 (20.5%) were diagnosed at stage I, 124 (23.7%) at stage IIA, 240 (45.9%) at stage IIB, while the remaining 52 (9.90%) were diagnosed with Stage III and IV disease. Within the study population, 39 (7.5%) women underwent radical hysterectomy alone, 110 (21.00%) underwent radical hysterectomy followed by adjuvant therapy, and 184 (35.14%) received primary radiotherapy or concurrent chemoradiation. A significant portion of CC cases presented at an early stage, underscoring the importance of an effective screening program to prevent advanced-stage disease and enhance early detection rates. Establishing a patient navigation system immediately after diagnosis is crucial to prevent the loss of follow-up and ensure timely treatment. It is imperative to enhance the healthcare system's capacity to ensure timely treatment for cancer patients.
Keywords: Bangladesh; cervical cancer; colposcopy; management; staging